Teng-Long-Bu-Zhong-Tang induces p21-dependent cell senescence in colorectal carcinoma LS174T cells via histone acetylation - Hu B; An HM; Wang SS; Zheng JL; Yan X; Huang XW; Tian JH (Dove Medical Press, 2017)
Bing Hu,1,2 Hong-Mei An,3 Shuang-Shuang Wang,1,2 Jia-Lu Zheng,1,2 Xia Yan,1,2 Xiao-Wei Huang,1,2 Jian-Hui Tian1,2 1Department of Oncology, Longhua Hospital, Shanghai University of Traditional Chinese Medicine, 2Institute of Traditional Chinese Medicine in Oncology, Shanghai Academy of Traditional Chinese Medicine, 3Department of Science and Technology, Longhua Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China Abstract: Teng-Long-Bu-Zhong-Tang (TLBZT) is a Chinese herbal formula for colorectal carcinoma treatment. TLBZT effectively induces cell senescence in colorectal carcinoma, accompanied by p21 upregulation. In this study, we further explored the role of p21 in TLBZT-induced cell senescence, as well as the mechanism by which TLBZT upregulates p21. Specific knockdown of p21 expression by small interfering RNA significantly attenuated TLBZT-induced cell senescence in human colorectal carcinoma LS174T cells. Silencing of p53 by small interfering RNA did not affect TLBZT-induced p21 upregulation. Meanwhile, TLBZT inhibited histone deacetylase activity. Furthermore, TLBZT increased acetylation levels of histone H3 and H4, enhancing their binding to the p21 promoter. These data suggested that TLBZT induces cell senescence in LS174T cells through a mechanism involving p21 upregulation via histone H3 and H4 acetylation. This study provides new insights into the application of TLBZT for colorectal carcinoma treatment. Keywords: colorectal carcinoma, TLBZT, cell senescence, p21, histone acetylation